Urban expansion of the largest cities in Bosnia and Herzegovina over the period 2000-2018 - Drašković, Branislav J. (Geographica Pannonica, 2021)
The paper analyses the databases Urban Atlas (UA), Imperviousness, and CORINE Land Cover (CLC) for the largest cities in Bosnia and Herzegovina (B&H). The UA database contains information for five functional urban zones with more than 100,000 inhabitants: Sarajevo, Banja Luka, Tuzla, Mostar, and Zenica. The Imperviousness database is related to the subclasses of the urban atlas because the impermeability percentage has been used for a more detailed classification within the discontinuous urban area. The CLC database provides insight into the intensity of expansion of these cities during three six-year periods: 2000-2006, 2006-2012, and 2012-2018. The research has been used to analyse the expansion of urban zones, the structure, and form of cities, and the impact of urban expansion on the surrounding area. The results of the research show that, despite the negative demographic trends, there is a trend of urban expansion in B&H, mainly overthe agricultural land. According to the CLC database in the period 2000-2018, artificial areas increased in spatial coverage from 1.35% to 1.7%, and urban fabric from 0.99% to 1.27%. The Imperviousness database shows that in 2018sealed areas covered 1.59% and built-up areas 0.8% of the territory of B&H. The 2013 census showed that the number of inhabitants in all five functional urban areas decreased compared to 1991, but despite that fact, the expansion of urban zones continues with a weaker or stronger intensity.So far, there has been no research on urban development based on the high-resolution layers UA and Imperviousness database in B&H, so that such research is the most significant contribution of this article.
Keywords: Urban Atlas, Imperviousness, CORINE LC, sprawl, B&H.